Global diversity and ecological function of parasites of Euphausiids - Gómez-Gutiérrez, Jaime; Kawaguchi, So; Morales-Ávila, José Raúl (Springer, 2017)
"This volume critically reviews all previously published work of parasites that interact with krill (order Euphausiacea) updating misconceptions and summarizing the diversity of epibionts, ectoparasites, mesoparasites and endoparasites that interact with these crustaceans. As far as we know, there is a lack of books about parasites of marine crustaceans not targeted to fisheries and aquaculture. Thus, this would be the most complete and integrative monograph of parasites of marine zooplankton and micro nektonic organisms worldwide. Krill form immense aggregations and serve as food for multiple planktonic and nektonic predators playing a crucial role in pelagic food web. Besides, several species are also used for human consumption. For these reasons there is a growing concern about the health issues that krill parasites may impose on other species, including us. This book provides a comprehensive review of parasites of a crustacean order that can extrapolate to potential parasites in other crustacean taxa worldwide"- Resumé vydavatel